Salinity Effect on Dry Mass Partitioning in Different Plant Parts and Ion Uptake in Leaves of Rice Mutants (Journal of Environmental Science and Natural Resources, 2015)
The Four levels of sodium chloride induced salinity levels, 0, 6, 9 and 12 dSm-1 were imposed at 25 days after planting of six rice mutants. Results indicated that morphological parameters such as plant height and leaf area, dry mass production in different plant parts such as root, stem, leaf and grain yield hill-1, physiological characters such as biological yield and harvest index, yield attributes such as number of effective tillers hill-1, number of grains panicle-1 and 1000-grain weight, mineral ions in leaves such as potassium and calcium were decreased with gradual increasing of salinity levels while number of non-effective tillers hill-1 and Na content of leaves were increased with increasing soil salinity. The highest value of the above parameters was observed in control and the lowest values of them were observed at 12 dSm-1. Generally genotypes having ability to exclude Na from leaves were found salt tolerant in respect of dry mass production in different plant parts and vice versa. Among the genotypes, the dry matter production and yield loss due to salinity was less in RM250-170 and RM250-2080 than that in the others, which further revealed that RM250-170 and RM250-2080 had a greater tolerance to salinity than RM350-130, RM300- 280, RM250-1080 and IRATOM. The rank of salinity tolerance was: RM250-2080 > RM250-170 > RM250-1080 > IRATOM > RM300-280 > RM350-130.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22073 J. Environ. Sci. & Natural Resources, 6(1): 239-245 2013